The Impact of Organoid to Assembloid Technology in Biomedical Research - Meiliana, Anna; Chouw, Angliana; Askandar, Retina Shyallala; Woran, Blessari Tesalonika; Latarissa, Irma Rahayu; Wijaya, Andi (The Prodia Education and Research Institute (PERI), 2026)
Organoids, three-dimensional, self-organized structures derived from pluripotent or adult stem cells, have revolutionized biomedical research by overcoming the inherent limitations of traditional 2D cultures and animal models. This review traces the evolution of organoid technology from initial studies to the contemporary